2019
DOI: 10.1101/569095
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Functional metagenomics-guided discovery of potent Cas9 inhibitors in the human microbiome

Abstract: 1 CRISPR-Cas systems protect bacteria and archaea from phages and other mobile genetic elements, 2 which use small anti-CRISPR (Acr) proteins to overcome CRISPR-Cas immunity. Because they are 3 difficult to identify, the natural diversity and impact of Acrs on microbial ecosystems is underappreciated. 4To overcome this discovery bottleneck, we developed a high-throughput functional selection that isolates 5 acr genes based on their ability to inhibit CRISPR-Cas function. Using this selection, we discovered ten… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 68 publications
7
30
0
Order By: Relevance
“…However, creating 'designer' inhibitors for specific gene editors and editing scenarios is very challenging as Acr proteins are small and lack any sequence and structural conservation to use for direct identification of desired modalities. To overcome these problems, approaches such as screening 13 self-targeting genomes (7,10,19) or metagenomic DNA (13,14) attempt to cast a wide net in the genomic space to identify novel Acr activities. A more direct method is to use a 'guilt-byassociation' search approach, which leverages the repeated observations that Acrs tend to coexist in similar operons and that the genomic neighborhood of several Acrs contain anti-CRISPR associated (aca) genes that are closely coupled with Acrs, and widespread in bacteria and MGEs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, creating 'designer' inhibitors for specific gene editors and editing scenarios is very challenging as Acr proteins are small and lack any sequence and structural conservation to use for direct identification of desired modalities. To overcome these problems, approaches such as screening 13 self-targeting genomes (7,10,19) or metagenomic DNA (13,14) attempt to cast a wide net in the genomic space to identify novel Acr activities. A more direct method is to use a 'guilt-byassociation' search approach, which leverages the repeated observations that Acrs tend to coexist in similar operons and that the genomic neighborhood of several Acrs contain anti-CRISPR associated (aca) genes that are closely coupled with Acrs, and widespread in bacteria and MGEs.…”
Section: Discussionmentioning
confidence: 99%
“…This motif is a prominent feature of aca genes, which were recently shown to negatively regulate the transcription of their own operon (16,34). The self-regulating activity of aca proteins was shown 14 to be mediated by a direct interaction between the HTH motif and promoter proximal sequences containing two inverted repeats (IR). Examining the promoter regions of AcrIIA13-15, we found that all of them also contain similar promoter-proximal IR sequences (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, compared with the previously identified Acrs, which were identified via sequence homology or a genetic context, AcrIIA7-10, which inhibits Cas9, were identified based on functional activity using a high-throughput approach from metagenomics libraries [57] (Table 1). Recently, Forsberg et al [58] independently developed a similar Acr search strategy to discover a newly potent Acr, named AcrIIA11, identified from a Lachnospiraceae phage and that inhibits spCas9 in bacteria and in human cells. Overall, this functional selection system offers a new strategy for discovering Acrs targeting desired Cas proteins, overcoming the limited availability of reference Acr families determined through computational discovery directed by genomic background or homology.…”
Section: Type II Anti-crispr Proteinsmentioning
confidence: 99%